HAIC as a potential therapy for esophageal cancer patients with liver metastasis: a retrospective cohort study - Dong, Fengxiao; Cao, Guang; Lu, Zhihao (Frontiers in Medicine, 2023)
Methods This was a single-arm historical cohort study of ESCC patients with synchronous or heterochronous LM between December 2014 and July 2021 at the Department of Gastrointestinal Oncology. The patients were treated with HAIC for LM, and regular image assessments were performed according to the judgment of the interventional physician. Liver progression-free survival (PFS), liver objective response rate (ORR), liver disease control rate (DCR), overall survival (OS), adverse events (AEs), treatment information, and basic characteristics were observed retrospectively. Results Overall, a total of 33 patients were enrolled in this study. All included patients received catheterized HAIC therapy, with a median of three (ranging from 2 to 6) sessions. The treatment response of liver metastatic lesions included partial response (PR) in 16 (48.5%) patients, stable disease (SD) in 15 (45.5%) patients, and progressive disease (PD) in two (6.1%) patients, for an ORR of 48.5% and a DCR of 93.9%. The median liver PFS was 4.8 months (95% confidence interval (CI): 3.0–6.6 months), and the median OS was 6.4 months (95% CI: 6.1–6.6 months). Patients who achieved PR at the liver metastasis site after HAIC were more likely to have a longer OS than those who achieved SD or PD. Grade 3 AEs occurred in 12 patients. The most common grade 3 AE was nausea, occurring in 10 (30.0%) patients, followed by abdominal pain in three (9.1%) patients. Only one patient showed grade 3 elevation of alanine aminotransferase (ALT)/aspartate aminotransferase (AST), and one patient suffered from grade 3 embolism syndrome AEs. Grade 4 adverse events, followed by abdominal pain, occurred in one patient. Conclusion Hepatic arterial infusion chemotherapy might be an option as a regional therapy for ESCC patients with LM, as it is acceptable and tolerable.